2020
DOI: 10.1212/wnl.0000000000009434
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline profiles differ in Parkinson disease dementia and dementia with Lewy bodies

Abstract: ObjectiveTo examine whether domain-specific patterns of cognitive impairment and trajectories of decline differed in patients with clinically diagnosed Parkinson disease dementia (PDD) (N = 29) and autopsy-confirmed dementia with Lewy bodies (DLB) (N = 58) or Alzheimer disease (AD) (N = 174) and to determine the impact of pooling patients with PDD and DLB in clinical trials targeting cognition.MethodsPatients were matched on demographics and level of global cognitive impairment. Patterns of cross-sectional per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 49 publications
3
68
1
1
Order By: Relevance
“…Of note, DLB and PDD share many pathological and clinical features and are usually considered as two clinical entities on a spectrum of Lewy body disease 8,11 . From a neuropsychological perspective, it has been shown that PDD and DLB may have different cognitive profiles, such as the presence of a more severe impairment in executive functions for PDD and in memory for DLB, and trajectories of cognitive decline, which appear to be more rapid for DLB in the language domain 145 . However, at the earliest stages of dementia, worse performance on tests of attention and executive functions and construc tive abilities has been observed in DLB than in PDD 146 .…”
Section: Parkinson Disease Dementiamentioning
confidence: 99%
“…Of note, DLB and PDD share many pathological and clinical features and are usually considered as two clinical entities on a spectrum of Lewy body disease 8,11 . From a neuropsychological perspective, it has been shown that PDD and DLB may have different cognitive profiles, such as the presence of a more severe impairment in executive functions for PDD and in memory for DLB, and trajectories of cognitive decline, which appear to be more rapid for DLB in the language domain 145 . However, at the earliest stages of dementia, worse performance on tests of attention and executive functions and construc tive abilities has been observed in DLB than in PDD 146 .…”
Section: Parkinson Disease Dementiamentioning
confidence: 99%
“…Conversely, treatments targeting tau (or perhaps ADNC more broadly) may affect memory and global cognition to a greater degree than executive/visuospatial measures. While recent work suggests that memory and language are most sensitive outcome measures of cognitive change in dementia with Lewy bodies relative to visuospatial and executive function in Parkinson’s disease dementia [ 55 ], the study did not aim to differentiate the impact of each pathology on cognition, but rather the nature of cognitive changes associated with each clinical diagnosis. Notably, dementia with Lewy bodies typically exhibit concomitant ADNC pathology, which may have driven the decline in memory and language in this particular study [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…While recent work suggests that memory and language are most sensitive outcome measures of cognitive change in dementia with Lewy bodies relative to visuospatial and executive function in Parkinson’s disease dementia [ 55 ], the study did not aim to differentiate the impact of each pathology on cognition, but rather the nature of cognitive changes associated with each clinical diagnosis. Notably, dementia with Lewy bodies typically exhibit concomitant ADNC pathology, which may have driven the decline in memory and language in this particular study [ 55 ]. As disease modifying therapies for specific neuropathology emerge, it will be increasingly important to utilize outcome measures directly impacted by that specific pathology rather than co-occurring pathologies, which is often the case in dementia with Lewy bodies.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the speed of cognitive deterioration between patients with pure AD and AD with co-pathology, but the presence of AD pathology in those that had LBD led to faster cognitive impairment [ 29 ]. Others reported that some patients initially diagnosed with DLB had enough AD pathology to be classified as AD as well, historically known as the Lewy body variant of AD [ 34 ].…”
Section: Dysautonomia As a Results Of Brain Co-pathologiesmentioning
confidence: 99%